2015
DOI: 10.4238/2015.june.8.9
|View full text |Cite
|
Sign up to set email alerts
|

Association analysis between SNPs in the 5'-flanking region of the chicken GRP78 gene, thermotolerance parameters, and tissue mRNA expression

Abstract: ABSTRACT. Glucose-regulated protein 78 (GRP78) is a molecular chaperone in the endoplasmic reticulum and can be induced by different kinds of environmental and physiological stress. Thus far, the role of the GRP78 gene in thermotolerance in chickens has not been investigated. In the present study, we detected sequence variations in the 5ꞌ-flanking region of the GRP78 gene and evaluated several thermotolerance parameters, such as T3, corticosterone, H/L ratio, and levels of CD3 + , CD4 + , and CD8 + T cells, to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Signi cant upregulation of Glucose regulated protein (GRP78) in intestinal tissue only observed in embryonic thermal conditioning group may be because of functional adaptations in terms of nutrient absorption at enterocyte level. Kong et al (2015) reported increased expression of GRP78 gene in different tissues with gradual exposure to heat stress in 8d old chicken due to tissue speci city of expression of this gene.…”
Section: Discussionmentioning
confidence: 98%
“…Signi cant upregulation of Glucose regulated protein (GRP78) in intestinal tissue only observed in embryonic thermal conditioning group may be because of functional adaptations in terms of nutrient absorption at enterocyte level. Kong et al (2015) reported increased expression of GRP78 gene in different tissues with gradual exposure to heat stress in 8d old chicken due to tissue speci city of expression of this gene.…”
Section: Discussionmentioning
confidence: 98%
“…For example, GRP78 is required for cell proliferation and apoptosis inhibition of embryonic fibroblasts [19], and BiP / GRP78 plays a key role in avian reovirus-mediated apoptosis [20]. However, a rare study examining GRP78 response to heat stress (35 °C) showed that GRP78 mRNA levels in chicken heart, liver, brain, and leg muscles first increased (peaking at 3 h) and then decreased after, suggesting that the protein may function in avian immune response as well [21]. This study found that intracellular HSPA5 overexpression did not directly affect the differential expression of antigenpresenting genes, but did accelerate and enhance LPS recognition by HD11.…”
Section: Discussionmentioning
confidence: 99%